Optimization of Nickel Electroplating on Low Carbon Steel for Corrosion Resistance using Immersion Corrosiontest with 3.5% NaCl - Parulian Siagian; Richard A.M. Napitupulu; Eko Yohanes Setyawan; Muhammad Fakhri Amadika (Jurnal POLIMESIN, 2023)
This research studied the corrosion resistance of low carbon steel that has been coated with nickel in NaCl solution by the Immersion Corrosion method with 3.5% NaCl liquid. Coating is done to increase the wear resistance of low carbon steel. The coating is done by electroplating process, with various voltages of 3V, 3.5V, 4V and 5V and the liquid is heated to a temperature of 44-60oC in the immersion time range of 30 minutes, 40 minutes and 50 minutes for each voltage variation. From the results of the study, it was found that the longer the immersion time in the electroplating process, the thicker the resulting layer with the addition of about 4 - 8µm for each difference in immersion time.